Semiosis of Artificial Intelligence and Social Development - A. Yu. Kolianov (Дискурс, 2022)
Introduction. The article analyzes the semiotic aspects of the representation of artificial intelligence in the socio-cultural space and their influence on the nature of social development. The spread and penetration of technologies into social and political processes using artificial intelligence (AI) is accompanied by active discussions in the socio-political environment. Artificial intelligence is considered as one of the most important resources of social and political development, so the desire of states, politicians and public organizations to determine the semantic framework of its public perception is understandable.Methodology and sources. The theoretical foundations of the work were the classic works on semiotics by Ch. S. Pierce, Ch. W. Morris, as well as theoretical works on modern political semiotics (I.V. Fomin, M.V. Ilyin and others). To work with the empirical base, analyzes of documents (reports and materials from UNESCO, the European Commission, the Royal Society of London, Stanford University), public opinion polls (VTsIOM), discourse analysis, semantic and content analysis of materials from Russian and foreign media were used.Results and discussion. As a result of the study, we found that the main contradiction that accompanies the understanding of artificial intelligence, its essence and purpose at all levels of socio-political discourse is the polarization of public ideas about AI as a control tool and (or) a development tool. The contextual fields were also outlined, within which further development of the semiosis of artificial intelligence is possible.Conclusion. To understand the nature of the representation of technologies using AI in socio-political discourse and to manage this process, an interdisciplinary approach and an appeal to the scientific potential of the social sciences and the humanities, in particular, semiotics, are appropriate, which makes it possible to study the semiosis of technology at the semantic, syntactic and pragmatic levels. It also seems promising to turn to a comparative analysis of cultural and historical traditions and national-state models of social management that specifically integrate AI into social processes.